The Disaster Taxon Lystrosaurus: A Paleontological Myth - Modesto, Sean P. (Frontiers in Earth Science, 2020)
The term ‘disaster species’ was a term originally conceived to describe marine microfossils that exhibited profound abundances in the wake of a biological crisis. The term was expanded in the 1990s to describe (as ‘disaster taxa’) opportunistic taxa that dominated their biota numerically (‘bloomed’) during the survival interval of a mass extinction event. The Permo-Triassic tetrapod genus Lystrosaurus has been cited regularly as a ‘disaster taxon’ of the end-Permian mass extinction. A review of the definitions that have been developed for disaster taxa, and data from recent biostratigraphic and phylogenetic studies that include species of Lystrosaurus, leads to the conclusion that the genus is not a ‘disaster taxon’. Further, the known biostratigraphy and tree topologies of species of Lystrosaurus do not satisfy more recent definitions that attribute diversification to disaster species. At most, species of Lystrosaurus that form the informal ‘Lystrosaurus abundant zone’ in the lower Katberg Formation, Lower Triassic of South Africa, could be described as opportunistic species.